2017
DOI: 10.17583/redimat.2017.2078
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical practice in textbooks analysis: Praxeological reference models, the case of proportion

Abstract: We present a new method in textbook analysis, based on so-called praxeological reference models focused on specific content at task level. This method implies that the mathematical contents of a textbook (or textbook part) is analyzed in terms of the tasks and techniques which are exposed to or demanded from readers; this can then be interpreted and complemented by a discussion of the discursive and theoretical level of the text. The praxeological reference model is formed by the analyst to categorize various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 11 publications
2
25
0
4
Order By: Relevance
“…Las praxeologías se utilizan, principalmente, en el análisis del material didáctico (e.g. Schivani, Brockington, & Pietrocola, 2013;Barbé, Espinoza, & Gellert, 2017;Wijayanti, & Winsløw, 2018;Wijayanti, 2019) y de la práctica en el aula (e.g. Barbé, Bosch, Espinoza, & Gascón, 2005;Corica, & Otero, 2011.…”
Section: Los Métodos De Enseñanza Como Organizaciones Praxeológicasunclassified
“…Las praxeologías se utilizan, principalmente, en el análisis del material didáctico (e.g. Schivani, Brockington, & Pietrocola, 2013;Barbé, Espinoza, & Gellert, 2017;Wijayanti, & Winsløw, 2018;Wijayanti, 2019) y de la práctica en el aula (e.g. Barbé, Bosch, Espinoza, & Gascón, 2005;Corica, & Otero, 2011.…”
Section: Los Métodos De Enseñanza Como Organizaciones Praxeológicasunclassified
“…A narrower research on how the notion of praxeology is used to analyse different types of tasks in textbooks was conducted by Wijayanti and Winsløw (2017) who found two themes in the arithmetical domain that were divided into seven specific types of tasks. Additionally, this research also showed that there were some dominant tasks that appeared in the textbooks.…”
Section: Textbooks Analysis Research Using the Atdmentioning
confidence: 99%
“…The example of table 1 illustrates the type of tasks T 6 . Wijayanti and Winsløw (2017) found seven types of tasks that are divided into two themes: 1. ratio and scale, and 2. direct and inverse proportion (table 2).…”
Section: Mathematical Praxeologies Of Proportionmentioning
confidence: 99%
“…That is, the knowledge block is a tuple (θ, Θ). Altogether, the theory of praxeology (fusion of "praxis" and "logos") is of a quadruple (T, , θ, Θ) and, thus, the praxeology block models an amalgam of human practice and knowledge [3,21,23,26,27].…”
Section: Analytical Frameworkmentioning
confidence: 99%